Evolutionary consequences of niche construction and their implications for ecology - Laland, K. N. (The National Academy of Sciences, 1999)
Organisms regularly modify local resource distributions, influencing both their ecosystems and the evolution of traits whose fitness depends on such alterable sources of natural selection in environments. We call these processes niche construction. We explore the evolutionary consequences of niche construction using a two-locus population genetic model, which extends earlier analyses by allowing resource distributions to be influenced both by niche construction and by independent processes of renewal and depletion. The analysis confirms that niche construction can be a potent evolutionary agent by generating selection that leads to the fixation of otherwise deleterious alleles, supporting stable polymorphisms where none are expected, eliminating what would otherwise be stable polymorphisms, and generating unusual evolutionary dynamics. Even small amounts of niche construction, or niche construction that only weakly affects resource dynamics, can significantly alter both ecological and evolutionary patterns.